Increasing knowledge and awareness of health workers and health cadres regarding congenital rubella syndrome in Imogiri II Bantul Primary Health Centre - Herini, Elisabeth Siti; Triono, Agung; Iskandar, Kristy; Prasetyo, Ashadi; Nuady, Albaaza; Hadiyanto, Marissa Leviani; Diantika, Kania; Wijayanti, Veronica Wulan; Damroni, Rais Aliffandy; Paramastuti, Avianti (Journal of Community Empowerment for Health, 2024)
Introduction: Prevention through campaign activities, Measles-Rubella (MR) vaccine introduction, and education play an essential role in controlling rubella and, eventually, Congenital Rubella Syndrome. A Community Engagement program was arranged collaboratively to improve the quality of promotive, preventive education by health workers and cadres and to improve the advanced management of Congenital Rubella Syndrome for health workers. Methods: A multi-method engagement program was conducted in collaboration with Imogiri II Bantul Primary Health Centre from March to October 2023. The program aimed to implement various activities involving health workers and health cadres. A descriptive study using the survey method was conducted to assess the knowledge level about Congenital Rubella Syndrome among health workers and cadres before and after the program. The survey included multiple-choice yes-no questions, and the results were analyzed using the McNemar test for paired nominal data with SPSS version 27. Results: We included 25 health workers and 28 health cadres. The results showed a significant increase in health worker's knowledge regarding the impact of Congenital Rubella Syndrome on various organs, including the brain, eyes, ears, heart, and child growth and development (p-values: 0.004, 0.004, 0.0004, 0.021, and 0.008, respectively). There was a notable improvement in health cadres' knowledge concerning the impact of CRS on the brain, eyes, ears, heart, child growth and development, and the child's quality of life (p-values: 0.007, 0.000, 0.000, 0.001, and 0.000, respectively). Conclusion: The community engagement program helps to enhance the knowledge of health workers and cadres concerning the impact of Congenital Rubella Syndrome on patients.